Gondolatok Borsod-Abaúj-Zemplén megye gazdaságfejlesztésének esélyeiről - Barta, Imre; Zsúgyel, János (Tér és Társadalom, 1988)
In the present study the authors present ideas about the economic development of the county having significant structural tensions. The earlier dynamically developing area showed simptoms of stagnation by the early 80s, what became an inconvenient source of tension both for the leaders of the county and those ot the country. The development came to a standstill primarily as a result of extensivedevelopment throughout the decades since, owing to the given natural resources, metallurgy, chemical industry, raw material industry and mining industry were developed while the development in the processing industry was neglected, thanks to the world market changes of the 70s. Agriculture of the county is characterized by poor soil and climatic properties, and the consequently low accumulating ability prevents investments into food industry, which would serve as a basis for further development, and thus hinders efficient employment of the area having a small village type structure of nettlement. The results of infrastructural development are contradictory: the developments connecting to big investments enabled production infrastructure to be constructed and very often at the cost of communal infrastructure. As regards human resources it is a great problem that professions comply with the one sided production structure. Having critically reviewed the economic development potential of the county the authors put forward their proposals for a better development. The lack of central resources is a basic hindering factor, which also means that local resources should be maximally mobilized. External resources are to be included in the development, structural change of the county only to the extent of the mobilizability of the resources of the territorial or economic units. In this case there is opportunity to join central programs for economic development, to include resources from other counties and countries. The resources should be used for easing territorial disproportions, structural one sidedness not forgetting, of course, that the county’s industry cannot be turned not even into one having processing character and not even in the long term. Cutting down market of unable production should go along with efforts to better utilize possibilities lying in establishments, buildings and infrastructure getting freed and efforts to locate branches that help to boom others. Significant aid may come from the mentai potential of the Miskolc Technical University for Heavy Industry and the introduction of innovation-oriented attitude in the higher education of specialists. Fodder-plant growing that–under the given climatic and cropland circumstances–is more suitable than cereals, animal husbandry based on it and food processing are to be promoted. Efficient production of low cost is to be introduced primarily by way of joining to various production systems. As regards infrastructural development, the main task here is to build out saving systems of transportation, energy network conditions for local industrial development, to strengthen the population retaining ability of the villages by decreasing housíng problems and introducing high level transport means. Individual initiation and venture should be given a wide scope in tertiary sector. Guaranteeing long-term safety for individual investments may transfer individual savings –instead of prestige consumptions–into the production sphere, thus becoming a new source of the county’s development. During the description of the means of the undelayable therapy the authors underline the role of local planning where making complex terrítorial plans should be subordinated to obtaining deeper knowledge of real territorial processes and to making informatorily better-established decisions on territorial development. In addition to economic conditions, great emphasis is laid on the release of mobilizable social energy. It is essential to replace execution-oriented attitude by an attitude oriented to individual venture and individual responsibility-taking both at the workbench and the writing-desk. To promote spatial diffusion of innovation processes it is decisive whether we can stop the migration of qualified labour and the worsening of the qualificatory exchange ratio, since without the inclusion of the human factor it is impossible to put an end to the gradual decline of Borsod-Abauj-Zemplén county’s economy and it will get to the periphery.